Outcomes of endometrial cancer prevention strategies in patients with Lynch syndrome: a nationwide cohort study in the NetherlandsResearch in context - Ellis L. Eikenboom; Lotte van Leeuwen; Floris Groenendijk; Jorien M. Woolderink; Anne M. Van Altena; Monique E. Van Leerdam; Manon C.W. Spaander; Helena C. van Doorn; Anja Wagner; M.C. Breijer; A.S. Tjalsma; F. Vork; et al. (EClinicalMedicine)
Summary: Background: Female Lynch syndrome carriers have an increased risk of developing endometrial cancer. Regardless, research on endometrial carcinoma tumorigenesis is scarce and no uniform, evidence-based gynaecological management guidelines exist. We therefore described gynaecological surveillance and surgery outcomes in a nation-wide Lynch syndrome cohort. Methods: For this retrospective cohort study, female Lynch syndrome carriers, prospectively registered in the Dutch Lynch syndrome database (StOET), were included up to February 28th 2022. Carriers were linked to the Dutch national pathology (PALGA) database. The number of carriers with/without gynaecological surveillance, number of index carriers with endometrial carcinoma before Lynch syndrome diagnosis were assessed, as well as uptake of risk-reducing surgery and characteristics of endometrial carcinomas including the requisite for adjuvant therapy according to current guidelines. Overall survival after endometrial carcinoma diagnosis was analyzed using Kaplan Meier time to event analyses, cumulative incidence was calculated after adjusting for competing risks (death and prophylactic hysterectomy). Findings: In total, 1046 registered female Lynch syndrome carriers were eligible for surveillance, of whom 313 (30.0%) did not have surveillance and 21.4% (n = 224 of 1046) opted for prophylactic hysterectomy. In carriers with surveillance, more cases of endometrial carcinoma and hyperplasia were found than in those without (37 endometrial carcinomas (7.3%) and 28 hyperplasias (5.5%) in 506 carriers with surveillance versus 14 (2.6%) and 4 (0.7%) in 540 carriers without surveillance, respectively); carriers with surveillance were generally younger than those without (median 56 years [IQR 48–65] versus median 65 years [IQR 49–75] at database assembly, respectively; p < 0.0001). Endometrial carcinomas were predominantly of endometrioid type and FIGO stage IA, regardless of surveillance. Adjuvant external beam radiotherapy was required in one patient in both groups. Overall survival after endometrial carcinoma diagnosis did not differ between carriers with or without surveillance or carriers with endometrial carcinoma before LS diagnosis (p = 0.51). For all endometrial carcinomas together, including index carriers, cumulative incidence was 22.7% at age 70. Interpretation: In a nation-wide cohort of Lynch syndrome carriers, nearly one-third of eligible carriers did not undergo gynaecological surveillance. Endometrial carcinomas diagnosed during surveillance were slightly more often stage FIGO IA, but this did not seem to substantially decrease the requisite for adjuvant therapy or affect overall survival, questioning effectiveness of current gynaecological management. Prospective research should further assess this, as well as patient preferences. Funding: None.